2017
DOI: 10.5539/ijc.v9n2p23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 50-Hz Sinusoidal Magnetic Field on the Production of Superoxide Anion and the Expression of Heat-shock Protein 70 in RAW264 Cells

Abstract: There is a growing concern if the power-line frequency (50/60 Hz) magnetic field (termed in this paper ELF-MF) increases cancer risks. Since one of the major causes of cancer is cellular oxidative stress, whether the ELF-MF increases the oxidative stress is a central problem in the studies on the biological effect of the ELF-MF. Here, we have investigated the effect of 50-Hz sinusoidal magnetic field on the production of O 2 -, the expression of heat shock protein (HSP) 70 and the mitochondrial membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The authors did unfortunately not investigate effects of coexposures to heat and MF. A recent study showed very similar results under comparable experimental conditions, with the exception that RAW mouse macrophages instead of human K562 cells were investigated ( 44 ).…”
Section: Summary and Concluding Remarksmentioning
confidence: 59%
See 1 more Smart Citation
“…The authors did unfortunately not investigate effects of coexposures to heat and MF. A recent study showed very similar results under comparable experimental conditions, with the exception that RAW mouse macrophages instead of human K562 cells were investigated ( 44 ).…”
Section: Summary and Concluding Remarksmentioning
confidence: 59%
“…MF-induced increases in HSP expression levels were also detected in a number of immune relevant cell lines: macrophages [RAW264 cell line ( 44 )], human leukemia and lymphoma cells [CEM, HL-60, U937, K562 cells, THP-1 cells ( 20 , 42 , 45 47 )]. Immune relevant cells or cell lines furthermore produce extracellular HSPs as a signal molecule for immune response [e.g., Ref.…”
Section: Elf-mf and Heat Shock Proteinsmentioning
confidence: 99%
“…It has to be pointed out that none of these studies differentiated between intra and intercellular HSPs. Enhancement of production and HSP70 expression by ELF-MFs (50 Hz, 0.1 or 0.5 mT) were also confirmed in RAW264 cells (an Abelson murine leukemia virus transformed cell line used as a macrophage model) ( 15 ). However, in other studies, with exposure of HL-60, H9c2, and Girardi heart cells to lower intensity MF and/or for shorter periods [60 Hz, 6.3 or 8.0 µT, 20 min ( 14 ); 50 Hz, 2 µT–4 mT, 15 or 30 min ( 12 )] no change in HSPs expression was detected.…”
Section: Do Emfs Affect Danger Signals Induction And/or Response?mentioning
confidence: 82%
“…These proteins are useful biomarkers that have already been used to monitor the impact of environmental factors on different invertebrate species (Singh & Lakhotia 2000, Mukhopadhyay et al 2002. MFs have been shown to induce increased transcription and translation of HSP70 (Malagoli et al 2006, Pooam et al 2017). Critical early steps in stress response induced by ambiental magnetic fields are activation of heat shock factors (HSF) and increased heat shock element (HSE) (Lin et al 1997).…”
Section: Stress Effects Of Ambiental Magnetic Fieldsmentioning
confidence: 99%